RELATIONSHIP BETWEEN MAXIMUM STRENGTH AND ERGONOMETRIC PERFORMANCE IN SELECTED CHILEAN ROWERS (Fiep Bulletin - online, 2014)
The aim of this study was to correlate the maximum strength of upper and lower limbs with ergometer performance test in 2000 meters in selected Chilean rowing. The sample consisted of 16 men of 20.37 ± 3.68 years old, 74.71 ± 5.07 and 179.35 kilograms of mass ± 4.15 cms. height called to the squad to participate Remo Chilean American Rowing Championship 2013. To identify the maximum dynamic strength in both lower limbs, as above, we used the test of 1 repetition maximum (1RM ) half squat (HS ) and horizontal rowing (HR ), in terms of performance in ergometer rowing (ER ), this was measured by test-specific test in the distance of 2,000 meters. The group presented a mean of 388 ± 9.5 seconds in the test of 2000 meters rowing ergometer, 119.12 ± 22.07 kg. HS raised in 1RM and 89.62 ± 14.24 kg in HR 1RM . The lasting time of exercise testing in 2000 mts. presents a correlation of -0.637 (p
Keywords: maximum strength; performance ergometer; rowing